Serum antibodies against Staphylococcus aureus can prognose treatment success in patients with bone infections. Issue 10 (25th December 2020) - Muthukrishnan, Gowrishankar; Beck, Christopher A.; Owen, John R.; Xie, Chao; Kates, Stephen L.; Daiss, John L.
Abstract: Prognosing life‐threatening orthopedic infections caused by Staphylococcus aureus remains a major clinical challenge. To address this, we developed a multiplex assay to assess the humoral immune proteome against S. aureus in patients with musculoskeletal infections. We found initial evidence that antibodies against some antigens (autolysins: Amd, Gmd; secreted immunotoxins: CHIPS, SCIN, Hla) were associated with protection, whereas antibodies against the iron‐regulated surface determinant (Isd) proteins (IsdA, IsdB, IsdH) were aligned with adverse outcomes. To formally test this, we analyzed antibody levels and 1‐year clinical outcomes of 194 patients with confirmed S. aureus bone infections (AO Trauma Clinical Priority Program [CPP] Bone Infection Registry). A staggering 20.6% of the enrolled patients experienced adverse clinical outcomes (arthrodesis, reinfection, amputation, and septic death) after 1‐year. At enrollment, anti‐ S. aureus  immunoglobulin G (IgG) levels in patients with adverse outcomes were 1.35‐fold lower than those in patients whose infections were successfully controlled ( p  < 0.0001). Overall, there was a 51%–69% reduction in adverse outcome risk for every 10‐fold increase in initial IgG concentration against Gmd, Amd, IsdH, CHIPS, SCIN, and Hla ( p  < 0.05). Notably, anti‐IsdB antibodies remained elevated in patients with adverse outcomes; for every 10‐fold change in the ratio of circulating anti‐Isd to anti‐Atl IgG at enrollment, there was a trending 2.6‐fold increased risk (odds ratio = 2.555) of an adverse event ( p  = 0.105). Moreover, antibody increases over time correlated with adverse outcomes and decreases with positive outcomes. These studies demonstrate the potential of the humoral immune response against S. aureus as a prognostic indicator for assessing treatment success and identifying patients requiring additional interventions.